Circadian Rhythm and Physical Fatigue Separately Influence Cognitive and Physical Performance in Amateur Athletes - Panagiota Karanika; Philip Gallardo; Themistoklis Tsatalas; Giannis Giakas; Panagiotis V. Tsaklis (Journal of Functional Morphology and Kinesiology)
Background/Objectives: Circadian rhythm (CR) influences various physiological functions, including physical and cognitive performance, which fluctuate throughout the day. The present study aimed to investigate the combined and separate effects of CR and physical fatigue on cognitive and physical performance. Methods: A sample of 18 amateur athletes was subjected to a series of tests at three different times of the day: morning, afternoon, and evening. Fatigue was induced following an isokinetic concentric exercise combined with a 20 min treadmill run, followed by assessments of selected physical and cognitive tasks. Results: A repeated measure ANOVA did not reveal an interaction between CR and fatigue in cognitive performance (p > 0.05). However, a significant main effect of fatigue was observed in visual reaction time (VisRT) across all three timepoints. Moreover, peak torque (PT) and the peak torque fatigue index (PTFI) showed significant differences between the three times of the day, peaking in the evening. Conclusions: Although we found no interaction between CR and the physical fatigue state on selected cognitive parameters at the three times of the day, a separate effect of fatigue on cognitive performance was identified. Additionally, physical parameters exhibited peak values occurring in the evening hours. Future research should further explore underlying mechanisms that potentially influence cognitive performance at different times of the day.